Myths and their role in culture (Revista ABRA, 2016)
In almost all religions, gods, primeval beings and creators of nature, are responsible for the existence of human culture. In some occasions myths explain the emergence of culture as a way to transcend the natural world. In that case, it is the prodigious actions of the gods that create human culture. However, discontinuity between nature and culture often results from a sin or the violation of a ban by gods or by humans, such as man’s banishment from paradise in the Bible or the origin of birth and death in the founding myth of Japan. Consequently, based on Lévi-Strauss, culture fills a void in nature and assumes the human order, taking what nature has left to chance. It is our hypothesis that the function of myth is to explain this void as well as to perform a logical operation that recovers the lost time that, according to Lévi-Strauss, does not exist in an historical-chronological sense: the origin of humankind. In addition, we will outline (following the ideas of Jacques Lacan) the hypothesis that myths also have a psychological function, by explaining castration in the Other and preserving the structure in the same operation as a complete whole.